Ultrabroadband Photodetector Based on Ferromagnetic van der Waals Heterodiode. (20th June 2022) - Hu, Xin; Hou, Jie; Dong, Qingsong; Liu, Zhiyi; Wang, Suofu; Wang, Fang; Tu, Yubing; Han, Tao; Li, Feng; Zhang, Zongyuan; Hou, Xingyuan; Wang, Shaoliang; et al.
Abstract: The discovery of 2D ferromagnetic (FM) van der Waals (vdW) semiconductors with narrow bandgap and p ‐type transport behavior makes them promising for infrared photodetection. Here, a 2D vdW heterodiode uncooled long‐wave infrared (LWIR) photodetector by stacking a p ‐type 2D FM material CrSiTe3 on top of an n ‐type transition metal dichalcogenides (TMDs) MoS2 is reported. A good rectification ratio > 10 2 and an ultra‐broadband photoresponse from 0.52 to 10.6 μ m are demonstrated. The photoresponsivity of up to 20.7 A W −1 and the external quantum efficiency (EQE) of up to 4031.7% are obtained under a 1310 nm laser at a − 1 V bias in ambient, which indicates that these CrSiTe3 –MoS2 p–n junction devices have a good photovoltaic response. Meanwhile, the photovoltaic responsivity up to 0.15 A W −1, EQE up to 29.7%, and fast response with a decay time of 2.8 μ s at 637 nm are demonstrated. In addition, the room temperature mid‐wave infrared (MWIR) specific detectivity and LWIR specific detectivity of CrSiTe3 –MoS2 is 6.1 ×  10 9  cm Hz 1/2  W −1 and 1.93 ×  10 9  cm Hz 1/2  W −1, respectively. These observations open up possibilities for developing high‐sensitive infrared detection based on the valley optical selection rule and LWIR image technology. Abstract : Highly sensitive uncooled long‐wave infrared photodetection based on the p‐type narrow bandgap ferromagnetic layered semiconductor CrSiTe3 . We design the vertical van der Waals heterojunction CrSiTe3 /MoS2 placed on a prefabricated metal mirror electrode realizing high photoresponsivity and fast response speed. A very low noise equivalent power of 10 −12 W/Hz 1/2, high D * of 1.4 × 10 11 cmHz 1/2 /W and ultra‐broadband response from 0.52‐10.6 μm were demonstrated.